Mechanical Transformation of Compounds Leading to Physical, Chemical, and Biological Changes in Pharmaceutical Substances - A. V. Syroeshkin; E. V. Uspenskaya; T. V. Pleteneva; M. A. Morozova; I. A. Zlatskiy; A. M. Koldina; M. V. Nikiforova (The Scientific World Journal)
This study demonstrates the link between the modification of the solid-phase pharmaceutical substances mechanical structure and their activity in waters with different molar ratio «deuterium-protium». Mechanochemical transformation of the powders of lactose monohydrate and sodium chloride as models of nutrients and components of dosage forms was investigated by the complex of physicochemical and biological methods. The solubility and kinetic activity of substances dispersed in various ways showed a positive correlation with the solvent isotope profile. Substances dissolved in heavy water were more active than solutes in natural water. Differential IR spectroscopy confirmed the modification of substituents in the sample of lactose monohydrate, demonstrating physicochemical changes during mechanical intervention. The biological activity of the compounds was determined by the method of Spirotox. The activation energy was determined by Arrhenius. Compared with the native compound, dispersed lactose monohydrate showed lower activation energy and, therefore, greater efficiency. In conclusion, proposed data confirm the statement that mechanical changes in compounds can lead to physicochemical changes that affect chemical and biological profiles.